Environmental Awareness and Green Trust Mediating Green Marketing’s Impact on Coconut Coir Product Purchases Behavior - Sapna Biby,; Nurainun ,; Rini Meiyanti ,; Ikramuddin,; Rika Annisa, (International Journal of Scientific Research and Management (IJSRM), 2024)
Recent years have seen a notable shift in consumer behavior towards sustainability, driven by heightened environmental awareness. This shift has significantly influenced purchasing decisions, particularly regarding green products like coconut coir-based items, valued for their eco-friendliness, biodegradability, and versatility. As consumers become more knowledgeable about environmental issues, they increasingly seek products that align with their values, leading to the rise of green marketing strategies. This research examines the role of environmental awareness and green trust in mediating the impact of green marketing on the purchasing behavior of coconut coir products. Utilizing both primary and secondary data, the study collected responses from 179 participants through a structured survey. Data analysis was performed using Partial Least Square Structural Equation Modeling (PLS-SEM) with SMART PLS 3.0 software. The analysis included two measurement models: the outer model assessed the validity and reliability of latent variables, while the inner model evaluated the relationships between them. Findings reveal that green marketing significantly enhances green buying behavior, environmental awareness, and green trust. Specifically, green marketing positively impacts purchasing behavior through both environmental awareness and green trust. In conclusion, this research demonstrates that green marketing effectively influences consumer behavior towards sustainable products. By fostering environmental awareness and building consumer trust, green marketing not only encourages the purchase of eco-friendly products but also contributes to a larger cultural shift towards sustainability.